Determinants of Private Label Attitude: Predicting Consumers’ Brand Preferences Using Psychographics - Weiß, Stefanie (Springer, 2015)
Various psychographic traits that most directly influence consumers’ private label attitudes are the focal point of Stefanie Weiss’ investigation. The author develops a comprehensive profile of psychographic predictors of attitude and identifies ways of translating these insights into managerial practice. Her conclusions thereby strongly contribute to understanding and describing purchasers of private labels and can be meaningfully applied to the management areas of brand positioning and market segmentation. The hypothesized relationships between consumers’ private label attitude and various psychographic traits are tested on a sample of German and Austrian consumers using an online questionnaire. Their response data are then analyzed using the multiple regression technique.